APLIKASI KALENDER KEHAMILAN DAN PERHITUNGAN MASA USIA KEHAMILAN BERBASIS ANDROID MENGGUNAKAN ALGORITMA NAEGELE - Yulia Darmi; Siti Admira; Agung Kharisma Hidayah; Pahrizal Pahrizal (UNIVED Press, 2022)
ABSTRACT : Pregnancy process becomes the center of special for families who are waiting for the presence of a loved child. Therefore, pregnant women often checj with the obstetrician to determine the development of fetus in the womb. The problem occurs mother who for prenatal check-ups are only given the fetus underweight. Determining the start of pregnancy and gestational age is important to be able to know within the progress of pregnancy. One of the ways to determine gestational age by knowing the first day of the last menstrual period (LMP). With the naegele method, tjis calculation can also be used to calculate the estimated day of birth. As an easy way to estimate the weight of the fetus is to measure the height of the uterine fundus (TFU). Therefore, based on the problems above, an android-based pregnancy calendar and calculation application of gestational age were made by using the Naegele algorithm. The pregnancy calendar and calculation application of gestational age are designed to make it easier for pregnant women to find out the estimated day or birth. The gestational age and normal fetal weight according to gestational age on an android smartphone. Keywords: Naegele, HPHT, estimated birth, gestational age, fetal weight.